Great Khali or opportunist? The Herald’s framing of Kalisto Pasuwa’s coaching credentials prior to and just after guiding Dynamos FC to their historic fourth consecutive PSL championship in 2014 - Nyamayedenga, Johannes (Midlands State University, 2017)
Football or soccer is the most followed sport across the globe, Zimbabwe included. It is plausible to submit that football has evolved from being a mere source leisure animating lives of millions across the world, to become both big business and an industry. While there is a significant number of studies exploring the nexus of football, politics and identity in modern Zimbabwe, studies on the interface between football and communication media are scarce. Dynamos Football Club, Zimbabwe’s most successful Premier Soccer team won four consecutive league titles from 2011-2014, under the guidance of former player and coach Kalisto Pasuwa. The success story attracted significant media attention across Zimbabwe’s media spectrum. This study largely informed by the framing theory, thus systematically explores the framing of Kalisto Pasuwa’s story in The Herald newspaper. Of specific interest to the dissertation is how exactly did the state controlled daily newspaper constructed Pasuwa’s coaching credential before and just after guiding Dynamos to their fourth consecutive league title in 2014. Methodologically, the research is largely qualitative utilising an interpretive prism. Purposively selected articles on Pasuwa published during the period under study were subjected to critical discourse analysis and semiotic analysis. Purposively selected sports journalists from the newspaper were also interviewed to complement findings from analysed texts. Empirical data collected by the study suggest that Pasuwa’s identity and coaching personality was fluid during the period under study. In essence, most stories portrayed him as a coaching genius in Zimbabwean history. However, though to a lesser extent another discourse could be noted downplaying Pasuwa’s achievement, suggesting that he was a mere opportunist.